Gender Disparities in Scholarly Productivity within Academic Otolaryngology Departments. Issue 2 (16th November 2012) - Eloy, Jean Anderson; Svider, Peter; Chandrasekhar, Sujana S.; Husain, Qasim; Mauro, Kevin M.; Setzen, Michael; Baredes, Soly
Abstract : Objective: To examine whether there are gender disparities in scholarly productivity within academic otolaryngology departments, as measured by academic rank and the h‐index, a published, objective measure of research contributions that quantifies the number and significance of papers published by a given author. Study Design and Setting: Analysis of bibliometric data of academic otolaryngologists. Methods: Faculty listings from academic otolaryngology departments were used to determine academic rank and gender. The Scopus database was used to determine h‐index and publication range (in years) of these faculty members. In addition, 20 randomly chosen institutions were used to compare academic otolaryngologists to faculty members in other surgical specialties. Results: Mean h‐indices increased through the rank of professor. Among academic otolaryngologists, men had significantly higher h‐indices than women, a finding also noted on examination of faculty members from other specialties. Men had higher research productivity rates at earlier points in their career than women did. The productivity rates of women increased and equaled or surpassed those of men later in their careers. Men had higher absolute h‐index values at junior academic ranks. Women academic otolaryngologists of senior rank had higher absolute h‐indices than their male counterparts. Conclusions: The h‐index measures research significance in an objective manner and indicates that although men have higher overall research productivity in academic otolaryngology, women demonstrate a different productivity curve. Women produce less research output earlier in their careers than men do, but at senior levels, they equal or exceed the research productivity of men.